STRATEGI KOMUNIKASI SATUAN TUGAS PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL (PPKS) DALAM MENSOSIALISASIKAN PERMENDIKBUDRISTEKNO. 30 TAHUN 2021 DI UNIVERSITAS RIAU - Putri, Sakilah Zahara; Susanti, Hevi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The University of Riau (UNRI) is the first university in Indonesia to establish a Sexual Violence Prevention and Handling Task Force (Satgas PPKS UNRI). This is due to a case of sexual violence at Riau University which was in the public spotlight in 2021. Cases of sexual violence continue to increase. The Communication Strategy carried out by the UNRI PPKS Task Force in socializing Permendikbudristek No. 30 of 2021 continues to be carried out by determining the communicator, determining the audience, choosing the message, and choosing the media used such as old media and new media and the effects caused. This research uses a qualitative method with a descriptive approach. Data collection was carried out by interviewing 6 informants, as well as conducting observations and documentation. And using data analysis techniques by reducing data, presenting data and drawing conclusions. Furthermore, data validity checks are carried out by increasing persistence and triangulation. The results showed that the UNRI PPKS Task Force has carried out various communication strategies in socializing Permendikbudristek No. 30 of 2021 to prevent sexual violence at Riau University. Communicators play a big role in providing education and influencing audiences to understand the forms of sexual violence as well as the prevention and handling of sexual violence, the discovery of students, educators and education personnel who do not participate in socialization, then the selection of informative, persuasive, and educative messages, as well as the selection of media used such as Instagram, podcasts, YouTube, TikTok, blogs, and news, aims to facilitate the dissemination of information to the academic community and campus residents and the positive effects caused by the socialization that has been carried out have an impact on increasing the understanding of the academic community.